2021
DOI: 10.1186/s12872-021-02446-z
|View full text |Cite
|
Sign up to set email alerts
|

Trend in survival after out-of-hospital cardiac arrest and its relationship with bystander cardiopulmonary resuscitation: a six-year prospective observational study in Beijing

Abstract: Background Out-of-hospital cardiac arrest (OHCA), a global health problem with a survival rate ranging from 2 to 22% across different countries, has been a leading cause of premature death for decades. The aim of this study was to evaluate the trends of survival after OHCA over time and its relationship with bystander cardiopulmonary resuscitation (CPR), initial shockable rhythm, return of spontaneous circulation (ROSC), and survived event. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Heterogeneity: research designs and provide more reliable results [4,20,21]. Therefore, the actual survival outcomes in China may be lower than that of our pooled results.…”
Section: Random Effects Modelmentioning
confidence: 81%
See 1 more Smart Citation
“…Heterogeneity: research designs and provide more reliable results [4,20,21]. Therefore, the actual survival outcomes in China may be lower than that of our pooled results.…”
Section: Random Effects Modelmentioning
confidence: 81%
“…Moreover, our subgroup analysis found that survival rates were affected by the number of participants in our meta-analysis, and the group with participants more than 500 was lower than that of group with participants less than 500. Large sample studies usually have better research designs and provide more reliable results [ 4 , 20 , 21 ]. Therefore, the actual survival outcomes in China may be lower than that of our pooled results.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of bystander CPR in China is less than 20%. Most victims received appropriate treatment only when EMS personnel arrived at the scene[ 15 ]. In the large cities of China, the average time from the emergency call to EMS arrival was 10 minutes[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bystander first-aid is a medical intervention behaviour in which the eyewitness initiates CPR before professional medical staff arrival, shortening the treatment time and improving treatment effects [10]. Besides, some studies reported that emergency response time, emergency telephone availability, patients' initial heart rhythm type, and out-of-hospital defibrillation are key factors that increase the survival rate [1,9,[11][12][13]. In addition, the composition of prehospital emergency physicians may be another critical issue.…”
Section: Introductionmentioning
confidence: 99%